1987
DOI: 10.1111/j.1365-2761.1987.tb01101.x
|View full text |Cite
|
Sign up to set email alerts
|

A bath challenge model for furunculosis in rainbow trout, Salmo gairdneri Richardson, and Atlantic salmon, Salmo salar L.

Abstract: A natural bath challenge method has been developed for furunculosis using Atlantic salmon, Salmo salar L., and rainbow trout, Salmo gairdneri Richardson. Fish were placed in an enclosed, continuously circulating tank system, supplemented with additional oxygen, the temperature raised gradually (overnight) to 15-16°C, a low dose of Aeromonas salmonicida (strain 184/186) introduced into the tank and the challenge maintained for 14 days. The challenge strain was characterized with respect to possible virulence fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

1988
1988
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 19 publications
1
11
0
Order By: Relevance
“…The following antigens were prepared (as described below) for immunisation or in vitro stimulation of leucocytes: (1) formalin killed Aeromonas salmonicida strain MT004, an avirulent strain lacking an A-layer ; (2) formalin killed A. salmonicida strain MT004 grown under iron restricted conditions ( Fe) (see below); and (3) formalin killed A. salmonicida strain MT423, a virulent strain possessing an A-layer (Adams et al, 1987). Aeromonas salmonicida strains MT004 and MT423 were inoculated into 3% tryptic soy broth (TSB, Gibco), and additionally strain MT004 was grown under iron restriction by inoculation into 3% TSB supplemented with 100 M 2,2 -dipyridyl (Sigma) (Hirst & Ellis, 1994).…”
Section: Antigensmentioning
confidence: 99%
“…The following antigens were prepared (as described below) for immunisation or in vitro stimulation of leucocytes: (1) formalin killed Aeromonas salmonicida strain MT004, an avirulent strain lacking an A-layer ; (2) formalin killed A. salmonicida strain MT004 grown under iron restricted conditions ( Fe) (see below); and (3) formalin killed A. salmonicida strain MT423, a virulent strain possessing an A-layer (Adams et al, 1987). Aeromonas salmonicida strains MT004 and MT423 were inoculated into 3% tryptic soy broth (TSB, Gibco), and additionally strain MT004 was grown under iron restriction by inoculation into 3% TSB supplemented with 100 M 2,2 -dipyridyl (Sigma) (Hirst & Ellis, 1994).…”
Section: Antigensmentioning
confidence: 99%
“…Protection is often tested by in vivo challenge models in which fish are exposed to virulent bacteria either by injection (Michel 1980;Nordmo 1997;Nordmo & Ramstad 1997) or by waterborne infection (immersion or cohabitation) (Cipriano 1982;McCarthy 1983;Adams et al 1987). Intraperitoneal injection is a reliable and reproducible way to challenge each fish with a uniform number of micro-organisms, but it fails to reflect the natural mode of infection and does not allow immune mechanisms located in other compartments, such as the skin, to respond.…”
Section: Introductionmentioning
confidence: 99%
“…Investigating several species, McCarthy (1983) claimed that smaller fish were more susceptible to furunculosis than larger fish. In contrast, Adams et al (1987) found that 8.5-g rainbow trout Oncorhynchus mykiss succumbed more rapidly to a bath exposure than 50-g fish, but that the plateau in the cumulative mortality rate curve occurred at a similar level. In drug efficacy trials using our Atlantic salmon model (Elston et al 1995), we found that the highest cumulative mortality rate among pathogen-inoculated but nonmedicated fish occurred with the largest fish.…”
Section: Discussionmentioning
confidence: 73%
“…Several authors have evaluated immersion, contact, and intragastric models for inducing furunculosis. As noted by McCarthy (1983) and Adams et al (1987), an immersion model is more realistic than an injection model for vaccine testing, because evaluation of preventative vaccines must take into account the full range of pathogen virulence during fish exposures and the full range of host defense mechanisms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation